Enhancing the Performance of Solution‐Processed n‐Type Organic Field‐Effect Transistors by Blending with Molecular "Aligners". (27th November 2013) - Zhang, Yue; Hanifi, David; Lim, Eunhee; Chourou, Slim; Alvarez, Steven; Pun, Andrew; Hexemer, Alexander; Ma, Biwu; Liu, Yi
<x xml:space="preserve">Abstract</x> A novel approach to enhancing the performance of solution‐processed n‐type organic field‐effect transistors by using trace amounts of molecular "aligners" to manipulate the assembly of "matrix" molecules in thin films is demonstrated. The device performance is one order of magnitude higher in 1wt% blended thin films than that in neat films, which correlates to an induced change of preferred orientation of the in‐plane π‐stacking molecules upon blending. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>